Guidance Magazines for Woman: Crisis, Stagnation, or Development - Dąbrowska-Cendrowska, Olga (Respectus Philologicus, 2015)
Female press is a broad segment of the press market. Some publications touch many topics, such as monthly Claudia, while others are dedicated to one specific field of everyday life, e.g., My cooking (Moje gotowanie) or I have a baby (Mam dziecko). Regardless of the release profile of the magazine, the press offer is addressed to women and based on the transmission of different types of advice adjusted to the prospective target group. Due to this offer, female readers can cope with all their problems and find answers to all the questions. The commercialization of the media is leading to the deepening of segmentation of female magazines, the goal of which is to reach the widest possible audience and achieve satisfactory results of the copy sales. This article attempts to answer the question what conditions the guidance bi-weekly and the guidance monthly magazines for women issued by companies with foreign capital, such as: Bauer Media Poland, Edipresse Poland, Burda Media Poland. The conclusions are drawn on the basis of data on the average copy sales published by the Association Press Distribution Control for the surveyed magazines.